A discovery system for narrative query graphs: entity-interaction-aware document retrieval - Hermann Kroll; Jan Pirklbauer; Jan-Christoph Kalo; Morris Kunz; Johannes Ruthmann; Wolf-Tilo Balke (International Journal on Digital Libraries, 2023)
Finding relevant publications in the scientific domain can be quite tedious: Accessing large-scale document collections often means to formulate an initial keyword-based query followed by many refinements to retrieve a sufficiently complete, yet manageable set of documents to satisfy one's information need. Since keyword-based search limits researchers to formulating their information needs as a set of unconnected keywords, retrieval systems try to guess each user's intent. In contrast, distilling short narratives of the searchers' information needs into simple, yet precise entity-interaction graph patterns provides all information needed for a precise search. As an additional benefit, such graph patterns may also feature variable nodes to flexibly allow for different substitutions of entities taking a specified role. An evaluation over the PubMed document collection quantifies the gains in precision for our novel entity-interaction-aware search. Moreover, we perform expert interviews and a questionnaire to verify the usefulness of our system in practice. This paper extends our previous work by giving a comprehensive overview about the discovery system to realize narrative query graph retrieval.
Keywords: 000; Narrative information access; Narrative queries; Graph-based retrieval; Digital libraries